Cerinichthys koelblae, gen. et sp. nov., from the Upper Jurassic of Cerin, France, and its phylogenetic setting, leading to a reassessment of the phylogenetic relationships of Halecomorphi (Actinopterygii). Issue 1 (2nd January 2018) - Ebert, Martin
ABSTRACT: Unknown, well-preserved fish specimens from the Upper Jurassic Plattenkalk of Cerin, France, found in the historical collection in Muséum d'Histoire Naturelle de Lyon, France, and from the excavation site of the Collections de Géologie, Université Claude Bernard Lyon 1, France, permit description of Cerinichthys koelblae, gen. et sp. nov. This new genus differs from all other Halecomorphi in the following combination of features: 27 caudal principal rays; 51 vertical scale rows; presence of broadened basal fin segments in the posterior rays of the pectoral, pelvic, anal, and dorsal fins and the median rays of the caudal fin; complete absence of vertebral centra in adult-sized individuals and multiple small scales in the median and ventral parts of the caudal peduncle. Investigations concerning the phylogenetic setting of the new genus Cerinichthys led to a proposal for a revision of the Halecomorphi, with Cerinichthys as a basal member of the new order Ophiopsiformes. The new family Ophiopsiellidae, as replacement for Ophiopsidae, within the Ophiopsiformes, are ganoin-scaled Halecomorphi with one horizontally elongated dorsal fin or two dorsal fins. The Ionoscopidae are proposed to belong in the Amiiformes, and the order Ionoscopiformes needs to be reconsidered. The more basal Halecomorphi with massive ganoin scales remain poorly known, compared with the more advanced halecomorph group of the Amiidae. Closer investigation of their morphology and taxonomic relationships is therefore important for understanding broader patterns of halecomorph evolution. http://zoobank.org/urn:lsid:zoobank.org:pub:0D13F672-DBC1-4484-AE30-7D360DCD3123 SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Ebert, M. 2018. Cerinichthys koelblae, gen. et sp. nov., from the Upper Jurassic of Cerin, France, and its phylogenetic setting, leading to a reassessment of the phylogenetic relationships of Halecomorphi (Actinopterygii). Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1420071.